1984
DOI: 10.1136/jcp.37.1.14
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical detection of Ca antigen in normal, dysplastic and neoplastic squamous epithelia of the human uterine cervix.

Abstract: SUMMARY Immunohistochemical staining was performed on biopsies and cytological samples from normal, dysplastic and neoplastic squamous epithelia using the monoclonal Ca 1 antibody. The results of staining 92 biopsies and 20 cytological samples are described and it is reported that positive staining with Ca 1 antibody was detected in normal, dysplastic and neoplastic epithelia.The role of the Ca 1 antibody in the study of cervical cancer is discussed. immunohistochemical procedure to detect the Ca antigen in ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1984
1984
1991
1991

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 4 publications
1
3
0
Order By: Relevance
“…However, anti-CCA and Ca-1 rarely stained normal glandular epithelium (only 1 of 35 samples in each case), as compared with the antibodies to CEA and EMA. The intensity and distribution of staining for the CEA, EMA, and Ca antigens was similar to that reported by other investigators [1,2,5,11,14]. The staining was often focal and mainly limited in the intraepithelial neoplastic lesions to the superficial and middle epithelial layers.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…However, anti-CCA and Ca-1 rarely stained normal glandular epithelium (only 1 of 35 samples in each case), as compared with the antibodies to CEA and EMA. The intensity and distribution of staining for the CEA, EMA, and Ca antigens was similar to that reported by other investigators [1,2,5,11,14]. The staining was often focal and mainly limited in the intraepithelial neoplastic lesions to the superficial and middle epithelial layers.…”
Section: Discussionsupporting
confidence: 88%
“…As a result, a variety of monoclonal and polyclonal antibodies have been produced which recognize several antigens reported to be present in squamous cancer cells of the uterine cervix [l-14]. Detection of epithelial membrane antigen (EMA), carcinoembryonic antigen (CEA), TA-4 antigen, the Ca antigen, and an antigen expressed on the basal cell layer of human skin and other epithelia (VM-2) have received the most recent attention [1,3,8,10,11]. While McGee et al [15] and others have suggested that the detection of these antigens may be of value in identifying neoplastic changes in cervical biopsy and cytology samples, there are conflicting data regarding whether some of these markers are uniformly present in preneoplastic lesions [ 16,171. Employing a panel of antibodies including a monoclonal antibody raised against an extract of squamous cell carcinoma of the cervix (anti-CCA [7]), we describe in this report the immunoperoxidase-staining patterns of normal endocervical glandular epithelium, squamous metaplasia, and intraepithelial neoplastic conditions.…”
Section: Introductionmentioning
confidence: 99%
“…• Willingham et al (25) reported that the TFR was found diffusely distributed on the cell surface, as well as concentrated in clathrin-coated pits or the cell surface , in intracellular endocytic vesicles (receptosomes) , in tubular elements of the trans-reticular Golgi system, and in microtubule-associated membranous elements. Lloyd et al (8) reported that basal cells of the normal uterine cervix were positive for TFR, but not parabasal cells. On the contrary, Tamura et al (21) reported that the basal cells were negative, while the parabasal cells were positive for TFR.…”
Section: Discussionmentioning
confidence: 99%
“…This year we published results from a larger series using Cal antibody and concluded that it does not have a significant role in the primary diagnosis or follow-up of neoplastic conditions of the cervix (Lloyd et al 1984a). …”
Section: Monoclonal Antibodies For the Histopathological Diagnosis Ofmentioning
confidence: 99%